2015
DOI: 10.1002/bem.21939
|View full text |Cite
|
Sign up to set email alerts
|

Variation in dielectric properties due to pathological changes in human liver

Abstract: Dielectric properties of freshly excised human liver tissues (in vitro) with several pathological conditions including cancer were obtained in frequency range 100 MHz-5 GHz. Differences in dielectric behavior of normal and pathological tissues at microwave frequencies are discussed based on histological information for each tissue. Data presented are useful for many medical applications, in particular nanosecond pulsed electroporation techniques. Knowledge of dielectric properties is vital for mathematical cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 40 publications
0
68
0
Order By: Relevance
“…At the same time, dielectric data analysis is conducted. The dielectric data may be fitted to numerical models for use in simulations and ease in reporting . Common models include the Debye and the Cole‐Cole models .…”
Section: Minimum Information For Dielectric Measurements Of Biologicamentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, dielectric data analysis is conducted. The dielectric data may be fitted to numerical models for use in simulations and ease in reporting . Common models include the Debye and the Cole‐Cole models .…”
Section: Minimum Information For Dielectric Measurements Of Biologicamentioning
confidence: 99%
“…The dielectric data may be fitted to numerical models for use in simulations and ease in reporting . Common models include the Debye and the Cole‐Cole models . The model parameters are optimised to match the data using techniques such as the least‐squares method or the genetic algorithm .…”
Section: Minimum Information For Dielectric Measurements Of Biologicamentioning
confidence: 99%
See 1 more Smart Citation
“…However, these applications require direct contact between the applicator, electrodes and the biological sample. Therefore, despite many applications, the methodology has considerable limitations such as the dependence of PEF distribution on the dielectric properties of the sample (Corovic et al, 2013; Peyman et al, 2015; Campana et al, 2016a; Liu et al, 2016), presence of electrochemical reactions in the electrode-electrolyte or tissue interfaces (Pataro et al, 2015) and the possibility of electrical breakdown between the electrodes (Guenther et al, 2015; Rubinsky et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Lazebnik et al [] reported that the difference in dielectric properties between malignant and normal adipose‐dominated breast tissues was considerable, with up to a 10:1 difference, whereas the difference between malignant and normal glandular/fibroconnective tissues in the breast was no greater than approximately 10%. In addition, dielectric characteristics may change significantly under various pathological states [Peyman et al, ] at different locations [Surowiec et al, ; Swarup et al, ], particularly between different stages of tumor development [Swarup et al, ]. One previous study by Swarup et al [] revealed an obvious increasing trend of dielectric properties with growing tumor staging in fibrosarcoma tissue.…”
Section: Discussionmentioning
confidence: 99%